PERANAN FORUM KERUKUNAN UMAT BERAGAMA DALAM MEMBINA KERUKUNAN UMAT BERAGAMA DI KOTA BENGKULU - Syahril Syahril (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
Abstract: This study raised the issue of the role of religious harmony forum and enabling and inhibiting factors in fostering religious harmony in the city of Bengkulu. From the results of this study indicate that there has been dialogue, socialization Joint Regulation of the Minister, gave a written recommendation on the request for the establishment of houses of worship, fostering inter-religious harmony, internal religious communities and religious groups and the government. But success in fostering religious harmony is still far from expectations and can be said to be ineffective, it can be seen still rarely do inter-religious dialogue, no socialization laws on religious harmony to society, there has been no specific action in order the house of worship that no permit. Supporting factors in fostering religious harmony awareness, motivation, mutual understanding and tolerance between religious communities, the support of the Mayor by providing secretariat building facilities. While the limiting factor in fostering religious harmony in the city of Bengkulu is the infrastructure is not yet complete, the attitude of religious communities to theology, the political interests that carry the name of religion, and attitudes toward religious fanaticism.